Comparison of Modified Posterior Sub-Tenon's vs. Trans-Septal Triamcinolone Injection for Non-infectious Uveitis. (4th July 2021) - McKay, K. Matthew; Borkar, Durga S.; Sevgi, Duriye Damla; Susarla, Gayatri; Papaliodis, George N.; Sobrin, Lucia
ABSTRACT: Purpose : To compare the safety and efficacy of trans-septal vs. modified posterior sub-Tenon's (PST) corticosteroid injections for noninfectious uveitis. Methods : Retrospective comparison of periocular triamcinolone injection by modified PST (n = 36) vs. traditional trans-septal (n = 79) techniques. Safety and efficacy outcomes were analyzed with regression models. Results : There was no significant difference in visual acuity improvement between the groups at 6 months. There were higher rates of vitritis resolution in the modified PST group but this was not statistically significant (85.7% vs 62.9%, p = .07). Intraocular pressure (IOP) elevation rate trended higher with the modified PST injection (21.9% vs 9.0%, p = .06), with no instances of glaucoma surgery in either group. Two modified PST injection patients with refractory IOP rises had IOP normalization after corticosteroid depot removal. One year cataract surgery rates were similar. Conclusion : Modified PST injection offers clinical efficacy but with possibly higher IOP response rate which could be managed with corticosteroid removal.